Analisis Determinan Kejadian Stunting Anak Balita Di Pedesaan Demak - Desi Wulandari; Kun Aristiati; J. Supadi (JURNAL RISET GIZI, 2016)
Background: Prevalence of stunting in Demak district 2015 was 29%, higher than central java prevalence. Stunting have will inhibit the development of cognitive and motoricamong children with negative impact in the next life. This study aims to determine risk of stunting of children under five year.Methods: We used data from the need assesment project from the Nutrion of Departement Health of Polytechnic Semarang. We used 420 children wich selected using simple random sampling. Risk factor for child stunting included factor from nutrition, physiological, illness, parenting, health behavior and socioeconomic incidence. Variable intake of energy and protein obtained by Food Recall 2 x 24 hours, the variable gender, maternal age, height mothers, diarrhea, respiratory infection, a child's weight, parenting, attitudes, knowledge, the use of iodized salt, vitamin A, large families, education, employment and pendapatan diperoleh using a questionnaire with interview method. Logistic regression was use to determine the risk factors.Results: We found 33,1% children was stunting. From the best model factors, the risk factor for the children in stunting is maternal high ≤ 145 cm (OR = 2,5; CI = 1,057 to 5,022), maternal knowledge of 80% (OR = 2; CI = 1,070 to 2,776), family do not use any of iodized salt in the household (OR = 8,5; CI = 4,979 to 13,541) and maternal education less than primary school (OR = 3,5; CI = 1,022 to 11,275).Conclusion: Determinan Factors that make children at risk for stunting is maternal high, maternal knowledge, families who do not use iodized salt in the household and maternal education less than primary school. There is a need to take height measurements regularly in health pos to monitor child stunting.